Reflexões acerca da diversidade cultural nas políticas para audiovisual brasileiro - Viana, Lívia Reginato David [UNESP]; Cardoso, Vivianne Lindsay [UNESP]; D'Arcadia, João Guilherme da Costa Franco Silva [UNESP]; Carvalho, Juliano Maurício de [UNESP] (Universidade Federal da Paraíba, 2019)
This article, point some questions about the audience, genres and languages of Brazilian audiovisual productions, discusses the unique case of the Murilo de Mendes Law and considering some prescriptions for the future of the sector in the country. The study was the result of a CNPq scientific initiation research whose objective was the identification and systematization of theoretical and methodological matrices of the Brazilian intellectual production on the cultural diversity in the Public Policies of Communication for the audiovisual of the period of ten years (from 2005 to 2015). The methodology used was an Integrative Review. A comprehensive analysis for society of interdisciplinary Communication Studies (Intercom).

Neste artigo, apontamos algumas questões acerca da audiência, gêneros e linguagens das produções audiovisuais brasileiras, discutiremos o caso singular da Lei Murilo de Mendes e ponderarmos acerca de algumas prescrições para o futuro do setor no país. O estudo foi resultado de uma pesquisa de Iniciação Científica financiada pelo CNPq que teve como objetivo a identificação e sistematização de matrizes teóricas e metodológicas da produção intelectual brasileira sobre Diversidade Cultural nas Políticas Públicas de Comunicação para Audiovisual do período de dez anos (de 2005 a 2015). A metodologia utilizada foi a Revisão Integrativa. A amostra selecionada para análise foram os artigos encontrados nos anais do congresso nacional anual da Sociedade Brasileira de Estudos Interdisciplinares da Comunicação (Intercom).
Reflections on cultural diversity in Brazilian audiovisual policies
Keywords: Culture; Communication; Políticas públicas; Comunicação; Cultura